Imperative Construction in English : a Syntactic Analysis - Hagen, Paula (My University, 2011)
In English, commands, requests, assertions, instructions, etc. are typically expressed by sentences called imperatives. Because English does not provide specific morphological markers to differentiate between imperatives and other constructions, speakers must rely on other factors in order to determine the intent of such an utterance. This study examined how imperative constructions work in English.
Color poster with text and images.
Keywords: English language--Imperative; Grammar, Comparative and general--Imperative; Posters